2018
DOI: 10.3390/ma11040505
|View full text |Cite
|
Sign up to set email alerts
|

Tribological Behavior and the Mild–Severe Wear Transition of Mg97Zn1Y2 Alloy with a LPSO Structure Phase

Abstract: Dry friction and wear tests were performed on as-cast Mg97Zn1Y2 alloy using a pin-on-disc configuration. Coefficients of friction and wear rates were measured as a function of applied load at sliding speeds of 0.2, 0.8 and 3.0 m/s. The wear mechanisms were identified in the mild and severe wear regimes by means of morphological observation and composition analysis of worn surfaces using scanning electron microscope (SEM) and energy dispersive X-ray spectrometer (EDS). Analyses of microstructure and hardness ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…There was evidently grain elongation near the surface at 140 N; such a large plastic deformation resulted in cracking of MML. These results tells that a steady sustention of MML on the worn surface plays an important role in keeping MW regime as described by other research works [18,22]. However, a high content of iron oxide in MML could result in cracking and spallation of MML and consequently high wear rate under low speed.…”
Section: Morphological and Chemical Analysis Of Worn Surfacessupporting
confidence: 72%
See 2 more Smart Citations
“…There was evidently grain elongation near the surface at 140 N; such a large plastic deformation resulted in cracking of MML. These results tells that a steady sustention of MML on the worn surface plays an important role in keeping MW regime as described by other research works [18,22]. However, a high content of iron oxide in MML could result in cracking and spallation of MML and consequently high wear rate under low speed.…”
Section: Morphological and Chemical Analysis Of Worn Surfacessupporting
confidence: 72%
“…From the view point of wear rate value at MSWT state, the wear rate at 140 N and 0.8 m s −1 was 30.45×10 -12 m 3 m −1 , which was essentially close to the wear rate values of several magnesium alloys under the same sliding speed. For example, the wear rates were 30.1×10 -12 m 3 m −1 at 160 N for Mg97Zn1Y2 alloy, 27.9×10 -12 m 3 m −1 at 160 N for Mg-3Al-0.4Si-0.1Zn alloy, and 23.7×10 -12 m 3 m −1 at 130 N for AZ91 [21,22,26]. However, the MSWT occurred at 120 N and 0.2 m s −1 was quite different from the wear performance for magnesium alloys and aluminum alloys.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings are in good agreement with past studies by Bongaerts et al (2007) and Goh et al (2010) . In addition, other previous works have shown that the dependence of friction coefficient on applied load between a lubricated rubber and steel track contact could be described by a linear equation given as 1/ μ = a + b / W , where a and b are constants ( Schallamach, 1952 ; Denny, 1953 ; Hua et al, 2017 ; Sun et al, 2018 ). This relationship suggests that friction coefficient approaches a constant value when the applied load or pressure is sufficiently high enough that the true asperities contact area eventually reaches a limiting value.…”
Section: Resultsmentioning
confidence: 99%
“…In a mild wear regime, wear proceeds in such a steady state that the resulting wear rate is allowable, and surfaces are only damaged slightly [ 9 , 10 ]. Recently, based on a comprehensive investigation conducted on mild–severe wear transition of AZ91 alloy by Chen and Alpas [ 11 ], a contact surface dynamic crystallization (DRX) temperature criterion for mild–severe wear transition of magnesium alloys during the room-temperature sliding wear was established in our previous studies, and it has been successfully applied to several magnesium alloys such as AZ31, AZ51, AS31 and Mg97Zn1Y2 alloys [ 12 , 13 , 14 , 15 ]. The mild–severe wear transition loads were well predicted under different sliding speeds using DRX dynamics.…”
Section: Introductionmentioning
confidence: 99%